2014
DOI: 10.3390/molecules191219880
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Novel Lectin from the Edible Mushroom Stropharia rugosoannulata

Abstract: Abstract:To date, only a few steroids have been isolated from the mushroom Stropharia rugosoannulata which can be cultivated. In this paper, a novel lectin (SRL) with a molecular weight of 38 kDa, and a unique IKSGVYRIVSWQGALGPEAR N-terminal sequence was isolated from S. rugosoannulata, which represents the first protein isolated from the mushroom. The purification methods included (NH4)2SO4 precipitation, ion exchange chromatography on CM-cellulose, Q-Sepharose, and SP-Sepharose, and gel-filtration on Superde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…This is also supported by recent studies where fungal antitumor proteins with deoxyribonuclease activity were reported. Antitumor proteins from Agrocybe aegerita, Pholiota nameko and Ramaria botrytis mushrooms which possessed deoxyribonuclease activity have been reported to exhibit potent antiproliferative activity and apoptosis-inducing effect on several human cancer cells such as neuroblastoma (SH-SY5Y), HeLa, breast adenocarcinoma (MCF7) and lung adenocarcinoma (A549) cells ( Chen et al, 2012 ; Zhang et al., 2014a ; Zhang et al., 2014b ; Zhou et al, 2017 ). Therefore, it is likely that the 230NA protein may have similar cytotoxic properties as with the other reported deoxyribonucleases which may also play a role in cytotoxicity of HMWp.…”
Section: Discussionmentioning
confidence: 99%
“…This is also supported by recent studies where fungal antitumor proteins with deoxyribonuclease activity were reported. Antitumor proteins from Agrocybe aegerita, Pholiota nameko and Ramaria botrytis mushrooms which possessed deoxyribonuclease activity have been reported to exhibit potent antiproliferative activity and apoptosis-inducing effect on several human cancer cells such as neuroblastoma (SH-SY5Y), HeLa, breast adenocarcinoma (MCF7) and lung adenocarcinoma (A549) cells ( Chen et al, 2012 ; Zhang et al., 2014a ; Zhang et al., 2014b ; Zhou et al, 2017 ). Therefore, it is likely that the 230NA protein may have similar cytotoxic properties as with the other reported deoxyribonucleases which may also play a role in cytotoxicity of HMWp.…”
Section: Discussionmentioning
confidence: 99%
“…The correct excision of a linker in the expression host might not have happened and this resulted in lower carbohydrate‐binding affinity. Rhinocelectin could probably also recognize and bind specific complex carbohydrates as few mushroom lectins isolated from Stropharia rugosoannulata , Russula lepida , and Pleurotus citrinopileatus were found to be inulin‐specific . Nonetheless, Rhinocelectin is still cytotoxic toward cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Rhinocelectin could probably also recognize and bind specific complex carbohydrates as few mushroom lectins isolated from Stropharia rugosoannulata, Russula lepida, and Pleurotus citrinopileatus were found to be inulin-specific. 18,57,58 Nonetheless, Rhinocelectin is still cytotoxic toward cancer cells. The cytotoxic activity of recombinant Rhinocelectin is demonstrated to be independent from its carbohydrate-binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was observed that Agaricus brasiliensis presented anxiolytic effects on ischemia-induced anxiety rats [105]. In addition, there were several components showing inhibitory activities toward HIV-1 reverse transcriptase, including three laccases from Pleurotus cornucopiae, Lentinus edodes and Ganoderma lucidum [106][107][108], four lectins from Hericium erinaceum, Russula delica, Pleurotus citrinopileatus and Stropharia rugosoannulata [109][110][111][112], respectively.…”
Section: Other Bioactivities Of Mushroomsmentioning
confidence: 99%